INFLUENCE OF CULTURAL CONDITIONS ON THE PROPERTIES OF LACTIC ACID BACTERIA (Proceedings of the YSU B: Chemical and Biological Sciences, 2023)
The effect of various lactoserum, nutrient compounds and growth conditions (temperature, time) upon the cultivation of lactobacteria and their antibacterial properties was studied. The obtained supernatants were shown to have different antibacterial activity and sensibility to temperature.
Keywords: lactobacteria; antibacterial properties; lactoserum; growth conditions